Influence of Feeding Cowpea (Vigna unguiculata) Leaves on the Performance of Vanaraja Laying Hen - Swain, Bijaya Kumar (Indian Journal of Animal Nutrition, 2018)
The study was undertaken to investigate the utilization of cow pea leaves in Vanaraja laying hens. Vanaraja laying hens (N=36, 25 weeks old)Â were randomly distributed into 3 equal groups (duplicated into 3 groups of 3 laying hens each ) on wire mesh floored cages and offered standard layer ration @ 125g/hen/day (T1), standard layer ration @75g/hen/day and cow pea leaves as fresh basis @ 75g/hen/day (T2) and standard layer ration @ 62.5g/hen/day with cow pea leaves @ 125g/hen/day (T3) for a period of 8 weeks. Results indicated that significant (P<0.05) reduction in egg production (dozen or kg) was observed in group fed 125g cow pea leaves/hen/day. However, laying hens fed 75g of fresh cow pea leaves/hen/day produced eggs (in dozen) similar to that of control group. Feed intake was significantly (P<0.05) reduced based on the dry matter intake due to feeding of cow pea leaves. Feed efficiency (feed intake in kg/dozen egg or feed intake in kg/kg egg mass) was significantly improved (P<0.05) in 1st group of laying hens fed cow pea leavesÂ @ 75g/hen/day. . Feed cost to produce dozen income generation due to significant reduction in feed cost without affecting their performance. egg was significantly lower (P<0.05) for both the experimental groups fed cow pea leaves. It may be concluded that cow pea leaves can be fed @ 75g/hen /day on fresh basis to Vanaraja laying hens for more income generation due to significant reduction in feed cost without affecting their performance.